Safety and pharmacokinetics of olokizumab, an anti‐IL‐6 monoclonal antibody, administered to healthy male volunteers: A randomized phase I study. Issue 5 (26th May 2014) - Kretsos, Kosmas; Golor, Georg; Jullion, Astrid; Hickling, Matthew; McCabe, Suzanne; Shaw, Stevan; Jose, Joby; Oliver, Ruth
<x xml:space="preserve">Abstract</x> Interleukin‐6 (IL‐6) is implicated in the pathophysiology of several inflammatory conditions. Olokizumab, a humanized anti‐IL‐6 monoclonal antibody, selectively blocks the final assembly of the IL‐6 signaling complex. A randomized, double‐blind, placebo‐controlled, phase I dose‐escalation study assessed the safety and tolerability of escalating single doses of olokizumab administered intravenously (iv) or subcutaneously (sc) to 67 healthy male volunteers. The pharmacokinetics, pharmacodynamics and immunogenicity of olokizumab were also assessed. Olokizumab was tolerated at doses up to 3.0 mg/kg sc and 10.0 mg/kg iv; the maximum tolerated dose was not reached. No serious adverse events or withdrawals as a result of treatment‐emergent adverse events were reported. Pharmacokinetic analysis showed that both maximum serum concentration and area under the concentration–time curve increased linearly with increasing dose. Mean terminal half‐life was 31.5 days (standard deviation 12.4 days). The bioavailability of the sc doses ranged from 84.2% to 92.5%. Rapid decreases in C‐reactive protein concentrations were observed, with no dose dependency.